Crude Protein Electrophoresis of Some Species of Annona in Nigeria - Folorunso, A. E.; Olorode, O. (2014)
Seeds of four species of Annona were collected from different latitudes and special ecological zones such as the wet forest, dry forest and derived savanna areas of Nigeria and the crude proteins were extracted and analysed by electrophoretic fractionation. The result shows that the band at 3.3 cm, 4.2cm and 4.7cm are common to the Annona species. Annona squamosa and A. reticulata have the highest number of common bands. The band at 1.4cm is common to both A. reticulata and A. muricata. The number and combination of protein bands were taxon-specific. These show the close genetic relationship of the species.